Flow-Compensated vs. Monopolar Diffusion Encodings: Differences in Lesion Detectability Regarding Size and Position in Liver Diffusion-Weighted MRI - Moldenhauer, Alessandra; Laun, Frederik Bernd; Seuß, Hannes; Bickelhaupt, Sebastian; Reithmeier, Bianca; Benkert, Thomas; Uder, Michael; Saake, Marc; Führes, Tobit (Tomography, 2025)
Background/Objectives: Diffusion-weighted imaging (DWI) of the liver is prone to cardiac motion-induced signal dropout, which can be reduced using flow-compensated (FloCo) instead of monopolar (MP) diffusion encodings. This study examined differences in lesion detection capabilities between FloCo and MP DWI and whether visibility depends on lesion size and position. Methods: Forty patients with at least one known or suspected focal liver lesion (FLL) underwent FloCo and MP DWI. For both sequences, b = 800 s/mm2 images were used to manually segment FLLs, which were then sorted by size and location (liver segment). The number of detected lesions, the sensitivity, and the contrast-to-noise ratio (CNR) were calculated and compared across sequences, sizes, and locations. Results: Significantly more lesions were detected using FloCo DWI compared to MP DWI (1211 vs. 1154; p < 0.001). In total, 1258 unique lesions were detected, 104 of which were identified only by FloCo DWI, and 47 of which only by MP DWI. The sensitivities of FloCo DWI and MP DWI were 96.3% (95% CI: 95.1–97.2%) and 91.7% (95% CI: 90.1–93.2%), respectively. The largest additional lesion found with only one of the two sequences measured 10.9 mm in FloCo DWI and 8.2 mm in MP DWI. In relative numbers, more additional FloCo lesions were found in the left liver lobe than in the right liver lobe (6.4% vs. 3.5%). The lesion CNR was significantly higher for FloCo DWI than for MP DWI (p < 0.05) for all evaluated size intervals and liver segments. Conclusions: FloCo DWI appears to enhance the detectability of FLLs compared to MP DWI, particularly for small liver lesions and lesions in the left liver lobe.
CRIS-Team Scopus Importer:2025-11-07
Keywords: diffusion-weighted imaging; flow-compensated; lesion detection; liver lesions; signal dropout